LISTENING COMPREHENSION IN TEACHING FRENCH AS A FOREIGN LANGUAGE - Наташа Радусин-Бардић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2010)
In teaching practice of French as a foreign language, the listening comprehension may cause problems to the speakers whose mother tongue is Serbian. In order to understand what makes this competence so difficult to achieve, an anonymous survey was conducted among the students of the Faculty of Philosophy in Novi Sad, studying French language and literature and among those who have chosen French as an optional language. Based on their responses, some conclusions may help to explain the difficulties in teaching practice of listening comprehension in French as a foreign language. These conclusions are explained separately (the dominance of the written code, the neglect of the importance of phonetic exercises and of the linguistic variability). The analysis of the survey is followed by some strategies for developing the competence of listening comprehension in French as a foreign language, based on the recent didactic studies, as well as by some suggestions for the additional exercises in listening comprehension competence made by the students.